Stem cells in the oral cavity - TORBAY, Chadi; KHALED, Fadl (International Arab Journal of Dentistry (IAJD), 2017)
Stem cells are unspecialized cells that are able to replicate repeatedly through cell division. Under certain conditions, they differentiate into cells with specialized functions providing an excellent tool for cell therapy especially in case of degenerative pathologies. There are two kinds o f stem cells: Embryonic and adult. The embryonic stem cells, also called pluripotent, are capable of differentiating into all cell types of the body whereas the adult stem cells are less versatile and more difficult to identify, to isolate and to purify. Compared to the embryonic stem cells derived from placenta or umbilical cord, adult stem cells are considered to be the only hope for those people who haven’t done cryopreservation or banking. Throughout this paper, an overview of the location of stem cells in the oral cavity will be presented emphasizing especially on their therapeutic potentials.